Determinants of Early Initiation of Breastfeeding among Mothers of Children Aged Less Than 24 Months in Northwestern Romania - Cozma-Petruţ, Anamaria (Nutrients, 2019)
Early initiation of breastfeeding (EIBF), defined as putting newborns to the breast within 1 h of birth, may have important benefits for both infant and mother. The aim of this study was to assess EIBF practices and its determinants in northwestern Romania. This cross-sectional study was conducted from March to June 2019, based on a sample of 1399 mothers of children aged less than 24 months. The sample was recruited from the community, from 29 cities and 41 communes distributed across the six counties of the northwestern region of Romania. Mothers responded by face-to-face interviews to a structured questionnaire. Multivariate logistic regression was used to identify factors independently associated with EIBF. Only 24.3% of the mothers initiated breastfeeding within 1 h of birth. Delivering at a private hospital (adjusted odds ratio (AOR): 5.17, 95% confidence interval (CI) 3.87, 6.91), vaginal delivery (AOR: 4.39, 95% CI 3.29, 5.88), mother–newborn skin-to-skin contact for 1 h or more (AOR: 55.6, 95% CI 23.0, 134.2), and breastfeeding counseling during antenatal visits (AOR: 1.48, 95% CI 1.12, 1.97) were factors associated with increased likelihood of EIBF. Overall, the practice of EIBF was poor. Targeting modifiable factors associated with EIBF may be used to improve early initiation practice.